Toward a safe and high performance quasi-solid-state structural battery - Chan, Kwok Kiong (2025)
The development of structural batteries has increased in recent years due to its simultaneous ability of energy storage and load-bearing capability. Carbon fibers (CF) are excellent candidates as electrode materials and current collectors for structural batteries due to their lightweight, electrical conductivity, and excellent mechanical properties. In this work, carbon fiber cathodes (CFC) were fabricated via vacuum filtration using carbon fibers as substrate with different cathode active materials comprising high voltage NMC-based cathode materials (NMC111, NMC622, NMC811) and LFP as control. Coupled with a nonflammable PVDF-HFP based gel polymer electrolyte (GPE) with a wide electrochemical stability window, the half-cell performances of the CFC-GPE were studied. A structural battery prototype in full cell configuration was constructed using NMC622-CFC || GPE || CF, with an outstanding capacity retention of 95.2% at ambient conditions at a 1C rate after 100 cycles. Despite repeated external loading on the structural battery, the mechanically robust structural battery was able to retain 99% of its original specific capacity. A functional prototype shaped as the external roof of a small, motorized toy car was used to power it for several runs, and it could also withstand external load while retaining structural integrity. Future vehicular structural support could potentially be designed to be multifunctional, increasing mass savings, volume efficiency, and effective vehicle range.